OXIDATIVE STRESS AND MENOPAUSE (REVIEW OF LITERATURE) - N. V. Semyonova (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The aim of this review is to analyze the literature about the functional state of lipid peroxidation - antioxidant protection system in menopausal women. The activity of free-radical oxidation of lipids in women with sex steroid deficiency depends on the version of its development. The activity of free-radical oxidation of lipids is within age normal range at physiological menopause but there is oxidative stress at pathological climax course that can be determined by genes. The most of works demonstrated deficiency of glutathione, melatonin and reduced glutathione peroxidase activity in menopausal women but data about the content of vitamins are very ambiguous and prove their connection with various pathologies. It should be noted that oxidative stress in perimenopausal women is regarded as a prognostic index of the severity of menopausal symptoms.